Relationship between spacing of pregnancy and incidence of anemia in Multipara - K Widyantara; Verawati Sudarma (World Nutrition Journal, 2023)
Indonesia has a high prevalence of anemia in pregnant women, generally caused by iron deficiency. Pregnancy spacing <2 years, especially in multiparas, can affect the incidence of anemia which can cause miscarriage, premature birth, prolonged labor due to uterine muscle fatigue during contractions, postpartum bleeding due to the absence of uterine muscle contractions (uterine atony) and shock.